Um Toolkit para Avaliação da Intrusão de Métodos de Injeção de Falhas - Barcelos, Patrícia Pitthan A.; Weber, Taisy Silva; Drebes, Roberto Jung (Anais do Workshop de Testes e Tolerância a Falhas (WTF); 2002: Anais do III Workshop de Testes e Tolerância a Falhas, 2002)
This paper presents implementation and experiments of fault injection used to validate mechanisms of fault tolerance in communication protocols with temporal restrictions. It describes two approaches. The first implements fault injection through modifications in the application libraries, which ones support the target protocol. The second approach uses operating system resources. Also, the paper shows practical experiments using the fault injectors to validate a timeout mechanism of a communication protocol. The fault injectors are part of the INFIMO project, a toolkit to fault injection experimentation developed under Linux platform.